If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7n = -4n + 27 Reorder the terms: 9 + -7n = 27 + -4n Solving 9 + -7n = 27 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. 9 + -7n + 4n = 27 + -4n + 4n Combine like terms: -7n + 4n = -3n 9 + -3n = 27 + -4n + 4n Combine like terms: -4n + 4n = 0 9 + -3n = 27 + 0 9 + -3n = 27 Add '-9' to each side of the equation. 9 + -9 + -3n = 27 + -9 Combine like terms: 9 + -9 = 0 0 + -3n = 27 + -9 -3n = 27 + -9 Combine like terms: 27 + -9 = 18 -3n = 18 Divide each side by '-3'. n = -6 Simplifying n = -6
| 4x-3=2x+25 | | 8x+34=18 | | (2)(3.14)(r)=7.41 | | 63+d=105 | | 16a+17b+4c+5c-5b-4a= | | (9+8)=68X | | 9x=3x-2 | | 18p+11q+p-4q-3p= | | -2x-3=4x+2 | | 2x+(3x/4)=11 | | 2X+2X=68 | | myles=lie | | 4(x^2+6)=168 | | 10y^7+35y^6+25y^5= | | 9-5y=37+2y | | 2x^2=-4+6x | | 500=6x^3+5x^2 | | 2x^2=-4+6 | | 10x+8=4x+25 | | 12m+4n-6m+9n= | | Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 |